问题 解答题
已知数列{an}中的相邻两项a2k-1,a2k是关于x的方程x2-(3k+2k)x+3k•2k=0的两个根,且a2k-1≤a2k(k=1,2,3,…).
(I)求a1,a3,a5,a7
(II)求数列{an}的前2n项和S2n
(Ⅲ)记f(n)=
1
2
(
|sinn|
sinn
+3)
Tn=
(-1)f(2)
a1a2
+
(-1)f(3)
a3a4
+
(-1)f(4)
a5a6
+…+
(-1)f(n+1)
a2n-1a2n
,求证:
1
6
Tn
5
24
(n∈N*)
答案

(I)方程x2-(3k+2k)x+3k•2k=0的两个根为x1=3k,x2=2k

当k=1时,x1=3,x2=2,所以a1=2;

当k=2时,x1=6,x2=4,所以a3=4;

当k=3时,x1=9,x2=8,所以a5=8时;

当k=4时,x1=12,x2=16,所以a7=12.

(II)S2n=a1+a2++a2n=(3+6++3n)+(2+22++2n)=

3n2+3n
2
+2n+1-2.

(III)证明:Tn=

1
a1a2
+
1
a3a4
-
1
a5a6
+…+
(-1)f(n+1)
a2n-1a2n

所以T1=

1
a1a2
=
1
6
T2=
1
a1a2
+
1
a3a4
=
5
24
.当n≥3时,Tn=
1
6
+
1
a3a4
-
1
a5a6
+…+
(-1)f(n+1)
a2n-1a2n
1
6
+
1
a3a4
-(
1
a5a6
+…+
1
a2n-1a2n
)
1
6
+
1
6•22
-
1
6
(
1
23
+…+
1
2n
)
=
1
6
+
1
6•22
-
1
24
(1-
1
2n-3
)> 
1
6

同时,Tn=

5
24
-
1
a5a6
-
1
a7a8
+…+
(-1)f(n+1)
a2n-1a2n
5
24
-
1
a5a6
+(
1
a7a8
+…+
1
a2n-1a2n
)
5
24
-
1
9•23
+
1
9
(
1
24
+…+
1
2n
)
=
5
24
-
1
9•23
+
1
9
1
23
(1-
1
2n-3
)< 
5
24

综上,当n∈N*时,

1
6
Tn
5
24

单项选择题
问答题